Associations Between Emotional Intelligence and Personality Traits Among Socially Active Students - Людмила А. Дикая; Юлия В. Обухова; Валерия А. Егорова; Илья Н. Егоров (Rossijskij psihologičeskij žurnal., 2020)
Introduction. This study is a first exploration of associations between emotional intelligence and personality traits in a new generation of socially active students. The authors consider associations of emotional intelligence and personality traits both on levels of domains and facets. Methods. The study sample comprised 132 students of Southern Federal University aged 17–25 years (80 females and 52 males). All the respondents were representatives of socially active youth; they took an active part in professional and creative competitions, social projects, and self-assessed their level of social activity as high or above average. The study used the following psychological tests: (a) the EmIn inventory for assessing emotional intelligence by D. V. Lyusin and (b) the Big Five Inventory-2 modified by S. A. Schebetenko. The R software package for the nonparametric and parametric analysis was used for statistical data processing. Results and Discussion. Socially active students’ emotional intelligence had general (characteristic of all its components) and specific (characteristic of its individual components) associations with personality traits. General associations are those among ‘negative emotionality’ and ‘anxiety’ and all the structural components of emotional intelligence. Positive associations among ‘energy level’ and the components of emotional intelligence related to managing emotions, and negative ones among ‘emotional volatility’ and structural components of intrapersonal emotional intelligence (p ≤ 0.05) are classified as specific. The combination of negative emotionality and agreeableness affects general and interpersonal emotional intelligence; the combination of extraversion and negative emotionality affects intrapersonal emotional intelligence. Conclusion. The results can be applied for the development of students’ individual educational trajectories and recommendations for psychological and pedagogical support of students with leadership talent and special educational needs in social activity.